Temesvári és „bánsági” diákok a középkori európai egyetemeken - Petrovics, István (Per Aspera ad Astra, 2017)
This paper consists of five chapters. The first two deals with the medieval history of the Danube-Tisza-Mureș Interfluve (also known in the modern period as Bánság/Banat) and Temesvár (Timișoara). The author clarifies the fact that the regions urban development was different in a great extent than it was observed in other parts of the country. This was mainly due to geographical and ethnic reasons; however a decisive impact was clearly the ever growing advancement of the ottomans dated from the end of the 14th century. This even halted the development of the regions most advanced centre, the city of Temesvár. In the third chapter investigates the surroundings of Hungarian students who studied and visited universities abroad, using the latest research results on the field. In the fourth chapter, after a short introduction into the history of the medieval Hungarian universities – primarily the studium generale of Pécs – followes the overview history of the universities of Wien and Krakow, the two main destination points for the student from Temesvár and the Banat. The last chapter deals with the nature and peculiarity of the students from Temesvár and Banat, closing with a database.